Development of handheld induction heaters for magnetic fluid hyperthermia applications and in-vitro evaluation on ovarian and prostate cancer cell lines. (1st May 2023) - Castro-Torres, Jorge L; Méndez, Janet; Torres-Lugo, Madeline; Juan, Eduardo
Abstract: Objective: Magnetic fluid hyperthermia (MFH) is a still experimental technique found to have a potential application in the treatment of cancer. The method aims to reach around 41 °C–47 °C in the tumor site by exciting magnetic nanoparticles with an externally applied alternating magnetic field (AMF), where cell death is expected to occur. Applying AMFs with high spatial resolution is still a challenge. The AMFs from current and prospective MFH applicators cover relatively large areas; being not suitable for patients having metallic implants near the treatment area. Thus, there will be a clinical need for smaller magnetic field applicators. To this end, a laparoscopic induction heater (LIH) and a transrectal induction heater (TRIH) were developed. Methods: Miniature 'pancake' coils were wound and inserted into 3D printed enclosures. Ovarian (SKOV-3, A2780) and prostate (PC-3, LNCaP) cancer cell lines were used to evaluate the instruments' capabilities in killing cancer cells in vitro, using Synomag ® -D nanoparticles as the heat mediators. NIH3T3 normal cell lines were also used with both devices to observe if these cells tolerated the conditions applied. Results: Magnetic field intensities reached by the LIH and TRIH were 42.6 kA m −1 at 326 kHz and 26.3 kA m −1 at 303 kHz, respectively. Temperatures reached in the samples were 41 °C by the LIH and 43 °C by the TRIH. Both instruments successfully accomplished killing cancer cells, with minimal effects on normal cells. Conclusion: This work presents the first line of handheld medical induction heaters and have the potential to be a complement to existing cancer therapies. Significance: These instruments could enable the development of MFH modalities that will facilitate the clinical translation of this thermal treatment.